Ugh I’m going insane trying to do this. Please help.
![Ugh Im going insane trying to do this Please help class=](https://us-static.z-dn.net/files/da4/757a6aedfa21b42ff5c052772386315a.png)
Answer:
y(x)=6^(x)-3
Step-by-step explanation:
Let the exponential function be y(x) = ab^(x) but since the graph is translated 3 units down, y(x) = ab^(x)-3. Now, y(0)=-2=a*b^(0)-3. a=1. The equation is nearly complete but we need b, we can find it by using the point y(1)=3. y(x)=b^(x) - 3. y(1)=3=b-3, b=6. The equation of the function is y(x)=6^(x)-3